Considering Cumulative Social Effects of Technological Hazards and Disasters. (July 2020) - Gill, Duane; Ritchie, Liesel
This article describes research designs utilized to study cumulative sociocultural and psychosocial effects of technological hazards and disasters. We apply these designs to two cases: (a) the Exxon Valdez disaster with a focus on Cordova, Alaska, and (b) the Enbridge Northern Gateway Pipeline project with a focus on the Gitga'at First Nation in Hartley Bay, British Columbia, Canada. The Exxon Valdez oil spill began in 1989 with the grounding of the supertanker on Bligh Reef in Prince William Sound, Alaska. Fisheries collapsed, key species failed to recover, and litigation languished for 19 years, creating an accumulation of impacts from the initial event. The Gitga'at First Nation serves as a case for examining cumulative effects of energy development, specifically the Enbridge Northern Gateway Pipeline project proposed in 2010. Hartley Bay's sociocultural and psychosocial well-being are under threat from these and other ongoing development activities; they have also endured centuries of government-led subjugation. In studying each of these communities, we used mixed methods approaches that combined document review, observations, interviews, and surveys. Based on our experiences, we contend that the most effective way to examine cumulative social impacts is to employ concepts and theories drawn from existing research to support guidelines, frameworks, and methods.